No cabide: a percepção das digital influencers sobre a estratégia de design para otimização de protudos - Perpetuo, Nayara Chaves Ferreira (2017)
The present dissertation aims to identify if there is, and how broad can be, the gap between the project created from a strategy for the optimization of a product’s life, and the perception of digital influencers when using fashion products. Initially, an ethnographic approach was applied to reach this objective. The subjects of the research were four digital influencers who, besides consuming, support the dissemination of a consumer culture. A variety of questions related to consumption were important to this research, such as: the ephemerality and permanence of the artifacts, valorizing their symbolic aspects; the construction of identity from clothing; and the role of the researcher who, in the field, also influences the perception of the subjects of the research, as emphasized in the reflexive approaches of ethnography. It was possible to complement the research by expanding it to the application of the cartographic method. I have shown, through analyses, that the actions of the design strategy to optimize the life of fashion products are perceived by the digital influencers from an idea of sustainability. However, these actions are not entirely considered during the use, due to the valorization of the cultural and symbolic aspects, which make this the largest gap among project and use, design and consumer.